1996
DOI: 10.3354/meps132169
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification rates as measured by the isotope pairing method and by the acetylene inhibition technique in continental shelf sediments of the North Sea

Abstract: Denitrification rates in continental shelf sediments of the North Sea were measured by the simultaneous application of the acetylene inhibition technique (AIT) and the isotope pairing method (IPM). Nitrification was the predominant source of nitrate in these sediments. Both techniques were able to detect coupled nitrification-denitrification activity. Denitrification rates measured by the AIT were only measurable during the first 60 min of the incubation. Rates obtained by the AIT in this period ranged between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
58
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 20 publications
10
58
1
Order By: Relevance
“…This way, we obtain a denitrification rate of 1.94 mmol N m −2 d −1 or 2.43 mmol C m −2 d −1 , with an associated A T release of 2.29 mmol m −2 d −1 . In the North Sea, a tight coupling of nitrification and denitrification has indeed been reported by Lohse et al (1993) and Pätsch and Kühn (2008), and observed benthic denitrification rates in the SNS range from 1.6 to 4.6 mmol C m −2 d −1 (Lohse et al, 1996;Hydes et al, 1999), a range that centrally embraces our estimate here. Note that the coupling of ammonification, nitrification and subsequently denitrification does not lead to net production of A T .…”
Section: Input Parameter Expressionsupporting
confidence: 48%
“…This way, we obtain a denitrification rate of 1.94 mmol N m −2 d −1 or 2.43 mmol C m −2 d −1 , with an associated A T release of 2.29 mmol m −2 d −1 . In the North Sea, a tight coupling of nitrification and denitrification has indeed been reported by Lohse et al (1993) and Pätsch and Kühn (2008), and observed benthic denitrification rates in the SNS range from 1.6 to 4.6 mmol C m −2 d −1 (Lohse et al, 1996;Hydes et al, 1999), a range that centrally embraces our estimate here. Note that the coupling of ammonification, nitrification and subsequently denitrification does not lead to net production of A T .…”
Section: Input Parameter Expressionsupporting
confidence: 48%
“…This is in good agreement with the findings by Greenwood et al (2010), who observed bottom O 2 concentrations less than 6 mg O 2 L −1 in this area. As in region 3, the simulated benthic remineralisation rate lies at the lower end of the range of 5.6 to 30.6 mmol O 2 m −2 d −1 obtained from observational studies near this site (Lohse et al, 1996;Weston et al, 2008). This suggests that the model most likely underestimates benthic remineralisation rates.…”
Section: Spatial Variability In the North Sea Bottom O 2 Dynamicsmentioning
confidence: 78%
“…The imbalance was probably due to an underestimation of the used denitrification rates (van Beusekom et al 1999). Indeed, recent progress in the methodology of denitrification measurements show that early methods like the acetylene blocking method underestimate denitrification rates (van Luijn et al 1996;Lohse et al 1996;van Beusekom et al 1999). Based on available measurements and budgets, van Beusekom estimated an annual denitrification rate of about 600 mmol m -2 per year for the Wadden Sea.…”
Section: Interannual Variation In Nitrate Concentrationsmentioning
confidence: 99%